The communicative implications of the uniforms (Al-Academy, 2018)
The costume is a language that has carved itself into a path that is transformed over time in line with the development of human thought. The child theater is a form of communication between the individual and his society. The costume in the child's theater is seen as a sign of personality and identity. It is a model of communication that uses many of the world systems to which it belongs. Directed to the child by invoking the creative and creative energies of the designer in the formation of the children's theater. The second topic was the communicative function of secondary signs of uniforms and patterns of their transformations. The theoretical framework of the indicators included the on the research community. And his tools in the analysis of theatrical text in an intentional manner. The researchers used the descriptive analysis in dealing with the sample and then collected the results of the researchers in the with a set of conclusions and recommendations as well as a list of sources and references